The home dairy - Edwards, Elizabeth (My University, 1892)
Introduction: A supply of good milk and butter is among the necessities in every home. The many substantial and dainty articles of food made from these products makes it essential that they be palatable and unadulterated. In order, however, to obtain the best results from the dairy, it is important to consider wisely the erection of a convenient, well ventilated dairy building, and also a careful management of the milk after it is drawn until the cream is made into butter. A good dairy building is found wanting however, in the many farm-houses of today, and the milk that is supplied to the house is consequently strained into crocks and pans and placed on a shelf somewhere out of the way. The most convenient or common place is in a damp musty cellar where a little of everything is kept; as potatoes, turnips, cabbage, onions, the gradual decomposition of which makes the cellar a very unfit place to keep milk good and sweet. The dairy may be constructed as a separate building or it may be connected with the home. If there be a running stream not far from the house and from the cow stable, it would be to an advantage to build a dairy of moderate size near it. The dairy building should be partitioned off into a milk room, a butter room, and a small room where the dairy utensils might be washed.
Citation: Edwards, Elizabeth. The home dairy. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Dairy room; Architecture; Layout; Milk; Animal husbandry; Theses; Manuscripts (documents)